Drivers of land change: Human-environment interactions and the Atlantic forest transition in the Paraíba Valley, Brazil. (15th December 2016) - Silva, Ramon F.B. da; Batistella, Mateus; Moran, Emilio F.
Highlights: Proximity of forest remnants is highly important in forest regeneration dynamics. The Forest transition tends to occur first in marginal lands. Socioeconomic drivers play important roles in advanced forest transition stages. Forest transition process may require shifts in drivers over time. Abstract: Human societies constantly interact with the environment through mutual feedbacks and adaptations. The aim of this research was to analyze human and environmental dimensions so as to understand how the dynamic processes of land use and land cover change are contributing to the increase of forest cover observed between 1985 and 2011 in the Paraíba Valley, Brazil. The forestry sector, based on eucalyptus plantations, is given particular attention due to its role in these change processes. Multi-layer perception neural network (MPNN) models were adopted to evaluate the influence of independent variables in the process of the forest transition. Based on the model's results, we conclude that the process is conditioned by a set of biophysical and socioeconomic variables that operate during different historical periods and in different landscape settings. The proximity of Atlantic forest remnants was influential in the forest transition for the three periods analyzed: 1985–1995, 1995–2005, and 2005–2011. In the first period of change (1985–1995), topography was most influential. Between the periods of 1995–2005 and 2005–2011, the proximity to eucalyptus plantations was an important factor, indicating a high probability of native forest recovery occurring in the vicinity of these monocultural areas. The forest transition tends to occur in areas less suitable for agriculture at the outset, but as these areas are replaced by forest cover, socioeconomic drivers such as farm credit and economic development play important roles in forest recovery.